Psikologi Pendidikan Dalam Kegiatan Belajar Mengajar - Ina Magdalena; Bagus Tri Sutrisno; Hanif Abdul Jabbar; Muchamad Muhaemin Al-Azis; M. Astari Romahi; Nodianus Darmadi (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Educational psychology as a science that examines the problems of the soul and psychological activity of a person in relation to education as an interaction is a discipline that is quite important in examining the problems that interfere with or support the psyche of learners in the learning process, so that through understanding the mental state of students then the teacher can set and try to find a solution to the problem, so for this matter, it is fitting for a teacher to need to have comprehensive knowledge about the psychology of education so that learning can take place effectively and directed. With the existence of educational psychology, an educator will understand the differences in each student in learning activities and how an educator deals with student personality differences. Therefore, the role of educators in this case is very influential on the success of the learning process in schools. Competent educators in the perspective of educational psychology are educators who are able to carry out their profession in a responsible manner, so as to be able to apply psychological principles and all related to educational psychology.